Gender, Credit, and Firm Outcomes - Delis, Manthos D.; Hasan, Iftekhar; Iosifidi, Maria; Ongena, Steven (Journal of Financial and Quantitative Analysis, 2022)
Abstract Small and micro-enterprises are usually majority-owned by entrepreneurs. Using a unique sample of loan applications from such firms, we study the role of owners’ gender in bank credit decisions and post-credit-decision firm outcomes. We find that, ceteris paribus, female entrepreneurs are more prudent loan applicants than are males because they are less likely to apply for credit or to default after loan origination. The relatively more aggressive behavior of male applicants pays off, however, in terms of higher average firm performance after loan origination.